(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The article examines the first EU response to the economic consequences of the CoViD-19 crisis, consisting in a mix of measures including the loosening of state-aids and budgetary constraints on national economic policies, temporary purchases of national public debt by the European Central Bank, a set of loans assisted by conditionality and transfers of limited amount based on the EU budget. On the basis of this analysis, the article suggests that the CoViD-19 crisis does not seem to have prompted a reconsideration of the structure of the EU economic governance. In particular, the Union appears still structurally unable to develop meaningful forms of transnational solidarity.